Desain UI/UX Mobile App mengenai Pengelolaan Konten dengan Search Engine Optimization menggunakan Pendekatan User Centered Design - Rian Farta Wijaya; Randi Rian Putra (LKP KARYA PRIMA KURSUS, 2025)
The advancement of digital technology has increased the demand for learning media that are more adaptive and easily accessible, including in the field of content management based on Search Engine Optimization (SEO). This study aims to design a mobile education platform focused on presenting materials, guidelines, and basic simulations related to website content management using SEO principles. The design process adopts a user-centered design approach, which includes user needs analysis, learning flow development, interface design, and the creation of educational content structures. The resulting product is a conceptual design of a mobile application that provides learning modules, illustrations of SEO techniques, and interactive features to help beginners understand the steps involved in content optimization. The design outcomes indicate that integrating SEO concepts into a mobile platform can produce a learning medium that is more practical and easier to comprehend. This study contributes by providing a blueprint for a mobile education design that can be further developed into an effective digital learning application that meets the needs of the search engine optimization era.